2023
DOI: 10.1128/aac.01627-22
|View full text |Cite
|
Sign up to set email alerts
|

Drug Susceptibility Profiling of Prototheca Species Isolated from Cases of Human Protothecosis

Abstract: Prototheca are unicellular, achlorophyllous, yeast-like microalgae that occur in a wide range of natural habitats. At least five species have been implicated as the causative agents of opportunistic infections of men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, the activities of individual drugs vary significantly between different Prototheca species and among strains of the same species. 22 Moreover, several studies have demonstrated the beneficial effects of blue light on pathogenic species of Prototheca . 23 Additionally, the study by Jagielski et al demonstrated that silver nanoparticles (AgNPs) and 3-Bromopyruvate also exhibited positive effects on pathogenic species of the Prototheca genus.…”
Section: Discussionmentioning
confidence: 99%
“…However, the activities of individual drugs vary significantly between different Prototheca species and among strains of the same species. 22 Moreover, several studies have demonstrated the beneficial effects of blue light on pathogenic species of Prototheca . 23 Additionally, the study by Jagielski et al demonstrated that silver nanoparticles (AgNPs) and 3-Bromopyruvate also exhibited positive effects on pathogenic species of the Prototheca genus.…”
Section: Discussionmentioning
confidence: 99%